The perception of Emotional Intelligence in initial teacher training in Costa Rica - Retana Alvarado, Diego Armando (2021)
The objective of this study is the analysis of the perception about the Emotional Intelligence of prospective Costa Rican primary teachers at the beginning of their training in Science Teaching. The research was carried out with and incidental sample of 61 students enrolled in the subjects of Science in Primary Education I and III of the Primary Education Degree of the University of Costa Rica. The instrument consisted of a Likert type questionnaire called Emotional Intelligence Profile. The data were subjected to descriptive analysis and exploratory factor analysis. The results in the emotional expression dimension suggest difficulties in the expression and regulation of feelings.